CRITICAL STUDY OF COMMUNITY EMPOWERMENT BASED ON FOREST APPROACH IN ITTO VILLAGE MODELS CIAMIS REGENCY - Tri Sulistyati Widyaningsih; San Afri Awang (Pusbindiklat - LIPI, 2011)
This study aims to critisize the community empowerment approach conducted by International Tropical Timber Organization (ITTO) project in the villages model in Ciamis. This study use qualitative method. Datawere collected through interview, observation, and documentation. The result shows that the villages model tend to have the same stages of empowerment, the implementation of the approach using by ITTO project still far from the essence of empowerment because of one of selected group is a successfull group, the program carried out uniformly, top-down, and using manipulative participation. The critical solution suggested for the next similarproject, before the implementation, all stakeholders should have a common understanding about the appropriate approach of community empowerment.